DNA repair processes are critical mediators of p53-dependent tumor suppression. (July 2018) - Janic, Ana; Valente, Liz; Wakefield, Matthew; Stefano, Leon; Milla, Liz; Wilcox, Stephen; Yang, Haoyu; Tai, Lin; Vandenberg, Cassandra; Kueh, Andrew; Mizutani, Shinsuke; Brennan, Margs; et al.
Abstract It has long been assumed that p53 suppresses tumor development through induction of apoptosis, possibly with contributions by cell cycle arrest and cell senescence1, 2 . However, combined deficiency in these three processes does not result in spontaneous tumor formation as observed upon loss of p53, suggesting the existence of additional mechanisms that are critical mediators of p53-dependent tumor suppression function3–5 . To define such mechanisms, we performed in vivo shRNA screens targeting p53-regulated genes in sensitized genetic backgrounds. We found that knockdown ofZmat3, Ctsf andCav1, promoted lymphoma/leukemia development only when PUMA and p21, the critical effectors of p53-driven apoptosis, cell cycle arrest and senescence, were also absent. Notably, loss of the DNA repair geneMlh1 caused lymphoma in a wild-type background, and its enforced expression was able to delay tumor development driven by loss of p53. Further examination of direct p53 target genes implicated in DNA repair showed that knockdown ofMlh1, Msh2, Rnf144b, Cav1 andDdit4 accelerated MYC-driven lymphoma development to a similar extent as knockdown of p53. Collectively, these findings demonstrate that extensive functional overlap of several p53-regulated processes safeguards against cancer and that coordination of DNA repair appears to be an important process by which p53 suppresses tumor development. In vivo shRNA screens in sensitized genetic backgrounds identify p53-activated target genes involved in DNA repair that enable its tumor suppressor function.